Segmental infarction of the omentum: diagnosis by ultrasound. Issue 717 (July 1985) - Naraynsingh, V.; Barrow, R.; Raju, G. C.; Manmohansingh, L. U.
Abstract : Pre-operative diagnosis of segmental infarction of the omentum is difficult because of its rarity and non-specific clinical features. We present a case of omental infarction and suggest that ultrasound scan may be helpful in the diagnosis of this entity.